2021
DOI: 10.11591/edulearn.v15i1.17436
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the internationalisation strategy of higher education: A case of Muhammadiyah Higher Institution

Abstract: This article aimed to identify the inhibiting factors and the internationalisation strategy of higher education in Indonesia. The study deployed a qualitative based on the case study at Muhammadiyah Higher Education Institutions. Data collected through in-depth interviews with key respondents include the leader of Higher Education, Research and Development Council of Muhammadiyah, university chancellors, and International Affairs Office head. Findings illustrate the factors hindering the internationalisation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…These interactions encourage students to gain valuable experience with socialising across cultures and develop their cultural awareness. Jandevi and Zareen (2020), Kusumawati et al (2020), andSiregar et al (2021) have identified the challenges in internationalising education in certain countries, particularly in Indonesia, where universities are predominantly located in towns with a stronger sense of tradition. The education systems of different countries have notable variations in their cultural and religious values.…”
Section: Discussionmentioning
confidence: 99%
“…These interactions encourage students to gain valuable experience with socialising across cultures and develop their cultural awareness. Jandevi and Zareen (2020), Kusumawati et al (2020), andSiregar et al (2021) have identified the challenges in internationalising education in certain countries, particularly in Indonesia, where universities are predominantly located in towns with a stronger sense of tradition. The education systems of different countries have notable variations in their cultural and religious values.…”
Section: Discussionmentioning
confidence: 99%
“…One of the skills that have been emphasized for faculty members teaching at international universities is the English language, the medium through which they can not only communicate with foreign students but write quality scientific papers and attend international conferences (Barroga and Mitoma, 2019). These English courses should be explicitly tailored to faculty's needs so that many English-and online learning-related preferences are considered and many relevant challenges regarding instruction, assessment, and research (Nwokeji et al, 2016;Nazarzadeh Zare et al, 2018;Siregar et al, 2021) are compensated for this particular population.…”
Section: Introductionmentioning
confidence: 99%